Energy Conservation and Controlling Co2 Emission using WEC Algorithm in Datacenters - T, Sangeetha; T, Sujatha (International Journal of Engineering and Technology, 2018)
Around the global, extended dryness threatens the reliable electricity production which is critical for data center operations. Therefore the quantity of water consumed by the data centers is been increasing day by day ultimately leading to more CO2 emission which forms the major environmental threat. Hence, there arises a necessity of a load balancing factor with optimized time complexity for electricity production. To achieve this, an energy and workload management algorithm called WEC is proposed. This algorithm reduces the data centers long-term water consumption and dynamically dispatches the workload among distributed data centers. This algorithm also aims at reducing CO2 emission and time taken to complete the work.Â